Polyurethane barrier explosion suppression material with antistatic property as well as preparation method and application thereof
By introducing specific antistatic agents into the polyurethane explosion-repressing material, the formation of an aqueous film improves the antistatic performance, solving the problem of material electrostatic accumulation, maintaining material performance, and achieving improved safety and reliability.
Patent Information
- Application Number
- CN202411673966.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-21
- Publication Date
- 2025-03-18
AI Technical Summary
Polyurethane explosion-repressing materials tend to accumulate static charge under certain conditions, resulting in spark discharge and safety hazards. In addition, traditional methods of adding conductive fillers or surface-coated conductive coatings have problems such as material performance and poor durability.
Introducing specific antistatic agents to improve the antistatic properties of the material by forming a water film of hydrophilic groups and polar groups on the surface of the material, avoiding adverse effects on the material's performance.
It effectively solves the problem of electrostatic accumulation on the surface of the material, maintains the original performance of the material, and can effectively release static charge in a short period of time, maintains the volume resistivity at a low level, and has a low tensile strength loss rate.
Smart Images

Figure BDA0005146589250000101
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of explosion suppression materials, and in particular to a polyurethane barrier explosion suppression material with antistatic properties, and a preparation method and application thereof. Background Art
[0002] As modern transportation vehicles have increasingly higher safety requirements, fuel tank safety protection technology has also developed rapidly. Among the many safety measures, the use of polyurethane barrier explosion suppression materials as fillers for fuel tanks is an effective means of explosion prevention. This type of material can effectively reduce the risk of explosion of flammable gases in the fuel tank, reduce the flame propagation speed through physical isolation, and thus improve the overall safety of the vehicle or equipment. In recent years, with the advancement of materials science, the performance of polyurethane materials has been significantly improved, including but not limited to temperature resistance, chemical resistance, and mechanical strength.
[0003] Although polyurethane barrier explosion suppression materials play an important role in improving fuel tank safety, they still face some challenges in practical applications, especially the problem of their anti-static performance. Because polyurethane materials themselves have certain insulating properties, static charges are easily accumulated on the surface of the material under certain conditions (such as rapid refueling, temperature changes, etc.). When static electricity accumulates to a certain extent, it may cause spark discharge, which in turn ignites the oil-gas mixture and poses a safety hazard. In addition, this static electricity accumulation problem of polyurethane materials may also affect the vehicle's electronic system and interfere with normal operation.
[0004] In order to solve the antistatic problem of polyurethane barrier explosion suppression materials, the industry currently adopts two main technical routes: one is to add conductive fillers, such as carbon black, metal fibers, etc., to polyurethane materials to improve the conductivity of the material. Although this method can improve the antistatic performance of the material to a certain extent, too much conductive filler will change the basic properties of polyurethane materials, such as flexibility, density and cost, affecting its original barrier effect and scope of use. At the same time, the uniformity of the distribution of conductive fillers is also a difficult technical problem to overcome. Uneven distribution may lead to poor local conductivity and even form static accumulation points; the second is to perform special treatment on the surface of the material, such as coating with a conductive coating, to promote the rapid release of static electricity. Improving the antistatic performance of the material by coating with a conductive coating is a relatively direct method, but this method has poor durability. During long-term use, especially under harsh environmental conditions (such as high temperature, high humidity, corrosive media, etc.), the coating is easy to fall off or damage and lose its antistatic function. In addition, surface treatment will increase production costs, and for the complex internal structure of the fuel tank, achieving uniform spraying is also a major challenge.
[0005] To this end, the present application provides a polyurethane barrier explosion suppression material with antistatic properties, and a preparation method and application thereof. Summary of the invention
[0006] The present application provides a polyurethane barrier explosion suppression material with antistatic properties, a preparation method and an application thereof. By introducing a specific antistatic agent, the problem of static electricity accumulation caused by the insulating properties of traditional polyurethane materials is effectively solved, and the problems of material performance degradation and poor durability caused by the traditional method of adding conductive fillers or coating the surface with conductive coatings are avoided.
[0007] The technical solution adopted by this application to solve its technical problem is:
[0008] The first object of the present application is to provide a polyurethane barrier explosion suppression material with antistatic properties, comprising the following raw materials in parts by weight:
[0009] 100-150 parts of polyether triol, 60-80 parts of polyester polyol, 10-15 parts of isocyanate, 3-5 parts of foaming agent, 1-3 parts of stabilizer, 1-3 parts of catalyst, 5-10 parts of coupling agent, 10-15 parts of antistatic agent;
[0010] The preparation method of the antistatic agent comprises the following steps:
[0011] Ethylene glycol monovinyl ether and dimethyl maleate are uniformly mixed, dimethyl carbonate and 1% by weight of 2,2'-azobisisobutyronitrile of ethylene glycol monovinyl ether are added, and the mixture is reacted at 65° C. for 12 hours to obtain the antistatic agent.
[0012] In one or more technical solutions, the molar ratio of ethylene glycol monovinyl ether to dimethyl maleate is 1:1.
[0013] In one or more technical solutions, the polyester polyol is poly(ethylene glycol adipate diol). Specifically, the hydroxyl value of the poly(ethylene glycol adipate diol) is 56 mg KOH / g.
[0014] Specifically, the polyester structure of poly(diethylene glycol adipate) diol gives the material higher mechanical strength and hardness, making it stronger when subjected to external forces. In addition, the polyester structure of poly(diethylene glycol adipate) diol has good heat resistance and is suitable for use in high temperature environments.
[0015] In one or more technical solutions, the polyether triol is obtained by ring-opening polymerization of 1,2-propylene oxide using propylene glycol as an initiator. Specifically, the molecular weight of the polyether triol is generally 3000-4000.
[0016] Specifically, the long chain structure of polyether triol gives the material good flexibility and elasticity, making it difficult to break when subjected to external forces. Polyether triol has good hydrolysis resistance and chemical corrosion resistance, and is suitable for use in environments such as fuel tanks.
[0017] In one or more technical solutions, the isocyanate is polymethylene polyphenyl isocyanate.
[0018] Specifically, polymethylene polyphenyl isocyanate provides multiple isocyanate groups, which react with hydroxyl groups (-OH) to form urethane bonds (-NH-COO-), forming a three-dimensional network structure, and enhancing the mechanical properties and chemical resistance of the material.
[0019] In one or more technical solutions, the foaming agent is water.
[0020] Specifically, water reacts with isocyanate to generate carbon dioxide (CO2) gas, which causes the material to foam and form a porous structure.
[0021] In one or more technical solutions, the stabilizer is dimethyl silicone oil.
[0022] Specifically, dimethyl silicone oil can stabilize the bubbles formed during the foaming process, prevent the bubbles from bursting, and ensure uniform foaming of the material.
[0023] In one or more technical solutions, the coupling agent is a titanate coupling agent.
[0024] Specifically, the titanate coupling agent can improve the bonding between the antistatic agent and the organic matrix, and improve the mechanical properties and durability of the material; at the same time, the coupling agent helps to improve the dispersibility of the antistatic agent in the matrix, avoid the aggregation of the antistatic agent, and ensure the uniformity of the antistatic agent.
[0025] In one or more technical solutions, the catalyst is dibutyltin dilaurate.
[0026] Specifically, dibutyltin dilaurate can accelerate the reaction between isocyanate and hydroxyl, shorten the reaction time, and improve production efficiency. By adjusting the amount of dibutyltin dilaurate, the reaction rate can be controlled to ensure the uniformity and stability of the material.
[0027] The second object of the present application is to provide a method for preparing the antistatic polyurethane barrier explosion suppression material according to the first object, comprising the following steps:
[0028] S1. Preparation of antistatic agent
[0029] Ethylene glycol monovinyl ether and dimethyl maleate are uniformly mixed, dimethyl carbonate and 1% by weight of 2,2'-azobisisobutyronitrile of ethylene glycol monovinyl ether are added, and the mixture is reacted at 65° C. for 12 hours to obtain an antistatic agent;
[0030] S2. Foaming treatment
[0031] Take 100-150 parts of polyether triol, 60-80 parts of polyester polyol and 10-15 parts of isocyanate, put them into a reactor for thorough mixing, heat them to 55°C under a nitrogen environment, and react at 55°C for 2-3 hours; then add 3-5 parts of foaming agent, 1-3 parts of stabilizer, 1-3 parts of catalyst, 5-10 parts of coupling agent and 10-15 parts of antistatic agent into the reactor, mix them thoroughly, heat them to 110-120°C, and react for 10-20 minutes; after the reaction is completed, cool them to room temperature to obtain a polyurethane barrier explosion suppression material.
[0032] The third purpose of the present application is to provide an application of a polyurethane barrier and explosion-suppressing material with antistatic properties, that is, the polyurethane barrier and explosion-suppressing material provided by the first purpose or the polyurethane barrier and explosion-suppressing material prepared according to the preparation method provided by the second purpose is used as a filling material in a fuel tank.
[0033] The beneficial effects of this application are:
[0034] The polyurethane barrier explosion suppression material described in the present application introduces an antistatic agent, and the antistatic surface contains hydrophilic groups (such as hydroxyl-OH) and polar groups (such as carboxyl-COOH), which can form a layer of water film on the material surface and improve the antistatic performance of the material by adsorbing water molecules in the environment. The polyurethane barrier explosion suppression material not only solves the problem of static electricity accumulation on the material surface, but also avoids the problems of material performance degradation and poor durability caused by the traditional method of adding conductive fillers or coating the surface with conductive coatings.
[0035] The polyurethane barrier explosion suppression material described in the present application can effectively release static charge in a short time, and the static voltage decay time is less than 10 minutes; before and after fuel immersion, the volume resistivity is maintained at a low level, far below the standard upper limit; after fuel immersion, the tensile strength loss rate is less than 4%. DETAILED DESCRIPTION
[0036] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present application more clearly understood, the present application is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present application and are not used to limit the present application.
[0037] In this application, the term "and / or" describes the association relationship of associated objects, indicating that there may be three relationships. For example, A and / or B can mean: A exists alone, A and B exist at the same time, and B exists alone. A and B can be singular or plural. The character " / " generally indicates that the associated objects are in an "or" relationship.
[0038] In the present application, "at least one" means one or more, and "plurality" means two or more. "At least one of the following" or similar expressions refers to any combination of these items, including any combination of single items or plural items. For example, "at least one of a, b, or c", or "at least one of a, b, and c" can all represent: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, and c can be single or multiple, respectively.
[0039] It should be understood that in the various embodiments of the present application, the size of the serial numbers of the above-mentioned processes does not mean the order of execution, some or all of the steps can be executed in parallel or sequentially, and the execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of the embodiments of the present application.
[0040] The terms used in the embodiments of the present application are only for the purpose of describing specific embodiments, and are not intended to limit the present application. The singular forms "a", "said" and "the" used in the embodiments of the present application and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings.
[0041] The weight of the relevant components mentioned in the embodiment description of the present application can not only refer to the specific content of each component, but also represent the proportional relationship between the weights of the components. Therefore, as long as the content of the relevant components is proportionally enlarged or reduced according to the embodiment description of the present application, it is within the scope disclosed in the embodiment description of the present application. Specifically, the mass described in the embodiment description of the present application can be a mass unit known in the chemical industry such as μg, mg, g, kg, etc.
[0042] The terms "first" and "second" are used only for descriptive purposes to distinguish objects such as substances from each other, and should not be understood as indicating or implying relative importance or implicitly indicating the number of indicated technical features. For example, without departing from the scope of the embodiments of the present application, the first XX may also be referred to as the second XX, and similarly, the second XX may also be referred to as the first XX. Thus, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features.
[0043] Preparation Example 1
[0044] The preparation method of the antistatic agent comprises the following steps:
[0045] In a reactor, ethylene glycol monovinyl ether and dimethyl maleate (DMM) were mixed in a molar ratio of 1:1, 1.0 wt% of ethylene glycol monovinyl ether and 2,2'-azobisisobutyronitrile as an initiator were added, dissolved in dimethyl carbonate 10 times the weight of ethylene glycol monovinyl ether;
[0046] The mixture in the reactor was reacted at 65° C. for 12 hours; after the reaction, it was precipitated with a mixed solution of methyl tert-butyl ether and ethanol (5:1, volume ratio), then dissolved and washed three times with tetrahydrofuran (THF), and finally dried in a vacuum drying oven for 24 hours to obtain a purified antistatic agent.
[0047] After infrared characterization testing, it was found that:
[0048] At 3495cm -1 The characteristic peak of hydroxyl (-OH) was detected at 1720 cm -1 The carbonyl (C=O) characteristic peak of dimethyl maleate was detected at 3000-2800 cm -1 The characteristic peaks of CH on the methyl and methylene groups were detected at . These characteristic peaks indicate that the prepared antistatic agent contains hydrophilic groups (such as hydroxyl -OH) and polar groups (such as carboxyl -COOH) in the molecular chain, so it has antistatic function.
[0049] The antistatic agent prepared in Preparation Example 1 has antistatic function for the following reasons:
[0050] The antistatic agent molecular chain contains hydrophilic groups (such as hydroxyl -OH) and polar groups (such as carboxyl -COOH). These groups form a layer of water film on the surface of the material, which improves the antistatic performance of the material through the following mechanisms:
[0051] Adsorption of water molecules: Hydrophilic groups such as hydroxyl (-OH) and carboxyl (-COOH) can adsorb water molecules in the environment and form an extremely thin film of water molecules on the surface of the material.
[0052] Ionization: The water molecules in the water molecule membrane will be ionized to produce positive and negative ions. These ions can effectively increase the conductivity of the material surface, thereby accelerating the release of static charge.
[0053] Ion conduction: Hydrophilic groups can also adsorb ionizable impurities in the air, increase surface ion concentration, further improve the conductivity of the material, and release static charges through the ion conduction mechanism.
[0054] Conductive channels: Hydrophilic groups form conductive channels on the surface of the material, allowing static charges to migrate from the inside of the material to the surface and be released more effectively.
[0055] Tunnel effect: Inside the material, the hydrophilic group can promote the interaction between the conductive particles to form a conductive network. Under the action of thermal motion, electrons can cross the potential barrier formed at the interface of the resin layer and transmit to the adjacent conductive particles through the quantum tunneling effect, thereby generating tunnel current.
[0056] Example 1
[0057] The polyurethane barrier explosion suppression material with antistatic property comprises the following raw materials in parts by weight:
[0058] 100 parts of polyether triol (molecular weight 3000), 60 parts of polydiethylene glycol adipate diol, 10 parts of polymethylene polyphenyl isocyanate, 3 parts of water, 1 part of dimethyl silicone oil, 1 part of dibutyltin dilaurate, 5 parts of coupling agent (model OL-T999, CAS No.: 61417-49-0), and 10 parts of antistatic agent (from Preparation Example 1).
[0059] The preparation method of the polyurethane barrier explosion suppression material comprises the following steps:
[0060] Take 100 parts of polyether triol (molecular weight 3000), 60 parts of polydiethylene glycol adipate diol, and 10 parts of polymethylene polyphenyl isocyanate, put them into a reactor for thorough mixing, heat to 55°C under a nitrogen environment, and react at 55°C for 2 hours; then add 3 parts of water, 1 part of dimethyl silicone oil, 1 part of dibutyltin dilaurate, 5 parts of coupling agent (model OL-T999, CAS number: 61417-49-0), and 10 parts of antistatic agent (from Preparation Example 1) into the reactor, mix thoroughly, heat to 110°C, and react for 10 minutes; after the reaction is completed, cool to room temperature to obtain a polyurethane barrier explosion suppression material.
[0061] Example 2
[0062] The polyurethane barrier explosion suppression material with antistatic property comprises the following raw materials in parts by weight:
[0063] 150 parts of polyether triol (molecular weight 4000), 80 parts of diethylene glycol adipate diol, 15 parts of polymethylene polyphenyl isocyanate, 5 parts of water, 3 parts of dimethyl silicone oil, 3 parts of dibutyltin dilaurate, 10 parts of coupling agent (model: OL-T999, CAS No.: 61417-49-0), and 15 parts of antistatic agent (from Preparation Example 1).
[0064] The preparation method of the polyurethane barrier explosion suppression material comprises the following steps:
[0065] Take 150 parts of polyether triol (molecular weight 4000), 80 parts of diethylene glycol adipate diol, and 15 parts of polymethylene polyphenyl isocyanate, put them into a reactor for thorough mixing, heat to 55°C under a nitrogen environment, and react at 55°C for 3 hours; then add 5 parts of water, 3 parts of dimethyl silicone oil, 3 parts of dibutyltin dilaurate, 10 parts of a coupling agent (model: OL-T999, CAS No.: 61417-49-0), and 15 parts of an antistatic agent (from Preparation Example 1) into the reactor, mix thoroughly, heat to 120°C, and react for 20 minutes; after the reaction is completed, cool to room temperature to obtain a polyurethane barrier explosion suppression material.
[0066] Example 3
[0067] The polyurethane barrier explosion suppression material with antistatic property comprises the following raw materials in parts by weight:
[0068] 130 parts of polyether triol (molecular weight 3000), 70 parts of polydiethylene glycol adipate diol, 12 parts of polymethylene polyphenyl isocyanate, 4 parts of water, 2 parts of dimethyl silicone oil, 2 parts of dibutyltin dilaurate, 8 parts of coupling agent (model: OL-T999, CAS No.: 61417-49-0), and 13 parts of antistatic agent (from Preparation Example 1).
[0069] The preparation method of the polyurethane barrier explosion suppression material comprises the following steps:
[0070] 130 parts of polyether triol (molecular weight 3000), 70 parts of polydiethylene glycol adipate diol, and 12 parts of polymethylene polyphenyl isocyanate were put into a reactor for thorough mixing, heated to 55°C under a nitrogen environment, and reacted at 55°C for 2.5 hours; then 4 parts of water, 2 parts of dimethyl silicone oil, 2 parts of dibutyltin dilaurate, 8 parts of a coupling agent (model: OL-T999, CAS No.: 61417-49-0), and 13 parts of an antistatic agent (from Preparation Example 1) were added to the reactor, thoroughly mixed, heated to 115°C, and reacted for 15 minutes; after the reaction was completed, cooled to room temperature to obtain a polyurethane barrier explosion suppression material.
[0071] Example 4
[0072] The polyurethane barrier explosion suppression material with antistatic property comprises the following raw materials in parts by weight:
[0073] 110 parts of polyether triol (molecular weight 3000), 65 parts of polydiethylene glycol adipate diol, 11 parts of polymethylene polyphenyl isocyanate, 3.5 parts of water, 1.5 parts of dimethyl silicone oil, 1 part of dibutyltin dilaurate, 6 parts of coupling agent (model: OL-T999, CAS No.: 61417-49-0), and 11 parts of antistatic agent (from Preparation Example 1).
[0074] The preparation method of the polyurethane barrier explosion suppression material comprises the following steps:
[0075] Take 110 parts of polyether triol (molecular weight 3000), 65 parts of diethylene glycol adipate diol, and 11 parts of polymethylene polyphenyl isocyanate, put them into a reactor for thorough mixing, heat to 55°C under a nitrogen environment, and react at 55°C for 2 hours; then add 3.5 parts of water, 1.5 parts of dimethyl silicone oil, 1 part of dibutyltin dilaurate, 6 parts of coupling agent (model: OL-T999, CAS No.: 61417-49-0), and 11 parts of antistatic agent (from Preparation Example 1) into the reactor, mix thoroughly, heat to 110°C, and react for 20 minutes; after the reaction is completed, cool to room temperature to obtain a polyurethane barrier explosion suppression material.
[0076] Example 5
[0077] The polyurethane barrier explosion suppression material with antistatic property comprises the following raw materials in parts by weight:
[0078] 140 parts of polyether triol (molecular weight 3000), 75 parts of polydiethylene glycol adipate diol, 14 parts of polymethylene polyphenyl isocyanate, 4.5 parts of water, 2.5 parts of dimethyl silicone oil, 2.5 parts of dibutyltin dilaurate, 9 parts of coupling agent (model: OL-T999, CAS No.: 61417-49-0), and 14 parts of antistatic agent (from Preparation Example 1).
[0079] The preparation method of the polyurethane barrier explosion suppression material comprises the following steps:
[0080] Take 140 parts of polyether triol (molecular weight 3000), 75 parts of polydiethylene glycol adipate diol, and 14 parts of polymethylene polyphenyl isocyanate, put them into a reactor for thorough mixing, heat to 55°C under a nitrogen environment, and react at 55°C for 3 hours; then add 4.5 parts of water, 2.5 parts of dimethyl silicone oil, 2.5 parts of dibutyltin dilaurate, 9 parts of coupling agent (model: OL-T999, CAS No.: 61417-49-0), and 14 parts of antistatic agent (from Preparation Example 1) into the reactor, mix thoroughly, heat to 115°C, and react for 18 minutes; after the reaction is completed, cool to room temperature to obtain a polyurethane barrier explosion suppression material.
[0081] Comparative Example 1
[0082] The polyurethane barrier explosion suppression material comprises the following raw materials in parts by weight:
[0083] 100 parts of polyether triol (molecular weight 3000), 60 parts of polydiethylene glycol adipate diol, 10 parts of polymethylene polyphenyl isocyanate, 3 parts of water, 1 part of dimethyl silicone oil, 1 part of dibutyltin dilaurate, 5 parts of coupling agent (model OL-T999, CAS number: 61417-49-0).
[0084] The preparation method of the polyurethane barrier explosion suppression material comprises the following steps:
[0085] Take 100 parts of polyether triol (molecular weight 3000), 60 parts of polydiethylene glycol adipate diol, and 10 parts of polymethylene polyphenyl isocyanate, put them into a reactor for thorough mixing, heat to 55°C under a nitrogen environment, and react at 55°C for 2 hours; then add 3 parts of water, 1 part of dimethyl silicone oil, 1 part of dibutyltin dilaurate, 5 parts of coupling agent (model OL-T999, CAS number: 61417-49-0), and 10 parts of antistatic agent (from Preparation Example 1) into the reactor, mix thoroughly, heat to 110°C, and react for 10 minutes; after the reaction is completed, cool to room temperature to obtain a polyurethane barrier explosion suppression material.
[0086] Comparative Example 2
[0087] The polyurethane barrier explosion suppression material with antistatic property comprises the following raw materials in parts by weight:
[0088] 100 parts of polyether triol (molecular weight 3000), 60 parts of polydiethylene glycol adipate diol, 10 parts of polymethylene polyphenyl isocyanate, 3 parts of water, 1 part of dimethyl silicone oil, 1 part of dibutyltin dilaurate, and 10 parts of antistatic agent (from Preparation Example 1).
[0089] The preparation method of the polyurethane barrier explosion suppression material comprises the following steps:
[0090] Take 100 parts of polyether triol (molecular weight 3000), 60 parts of polydiethylene glycol adipate diol, and 10 parts of polymethylene polyphenyl isocyanate, put them into a reactor for thorough mixing, heat to 55°C under a nitrogen environment, and react at 55°C for 2 hours; then add 3 parts of water, 1 part of dimethyl silicone oil, 1 part of dibutyltin dilaurate, 5 parts of coupling agent (model OL-T999, CAS number: 61417-49-0), and 10 parts of antistatic agent (from Preparation Example 1) into the reactor, mix thoroughly, heat to 110°C, and react for 10 minutes; after the reaction is completed, cool to room temperature to obtain a polyurethane barrier explosion suppression material.
[0091] The polyurethane barrier explosion suppression materials prepared in Examples 1-5 and Comparative Examples 1-2 were subjected to the following performance tests, and the relevant test results are summarized in Table 1 below.
[0092] 1. Electrostatic voltage decay test
[0093] Charge the explosion suppression material to be tested to 5000V, start timing, and record the time required for the static voltage to drop from 5000V to 500V.
[0094] Test environment conditions
[0095] Temperature: 23℃±2℃
[0096] Relative humidity: 45%-55%
[0097] Electrostatic voltage decay time: The time from 5000V to 500V should not exceed 10 minutes.
[0098] 2. Fuel immersion test
[0099] Test method: Soak the explosion suppression material to be tested in fuel to simulate long-term fuel contact conditions.
[0100] Test conditions: Soak in fuel oil at 70℃±2℃ for 84 days.
[0101] The volume resistivity and tensile strength of the explosion suppression material to be tested are measured before and after the test.
[0102] Performance indicators:
[0103] After the test, the tensile strength of the explosion suppression material to be tested should not decrease by more than 40%; the volume resistivity should not exceed 5*10 12 Ω·cm.
[0104] Table 1
[0105]
[0106] From Table 1, we can see that:
[0107] 1. The polyurethane barrier explosion suppression materials prepared in Examples 1 to 5 have the following properties:
[0108] 1. Excellent antistatic performance
[0109] It can effectively release static charges in a short time, and the static voltage decay time is less than 10 minutes, which meets the standard requirements.
[0110] 2. Stable electrical conductivity
[0111] Before and after fuel immersion, the volume resistivity remained at a low level, far below the standard upper limit, indicating that the material can still maintain good conductivity under conditions of long-term contact with fuel.
[0112] 3. Good mechanical properties
[0113] After fuel immersion, the tensile strength loss rate was less than 4%, indicating that the material has high mechanical strength and can maintain stable performance in practical applications.
[0114] The polyurethane barrier explosion suppression material of Comparative Example 1 has significant differences in performance from that of Example 1, which is mainly reflected in the following aspects:
[0115] 2. Comparative Example 1 is compared with Example 1:
[0116] 1. Static voltage decay time
[0117] Comparative Example 1: The static voltage decay time is greater than 20 minutes.
[0118] Embodiment 1: The static voltage decay time is less than 10 minutes.
[0119] 2. Volume resistivity before and after fuel immersion
[0120] Comparative Example 1:
[0121] Volume resistivity before immersion: 1.1*10^13Ω·cm
[0122] Volume resistivity after immersion: 2.6*10^15Ω·cm
[0123] Embodiment 1:
[0124] Volume resistivity before immersion: 5.1*10^8Ω·cm
[0125] Volume resistivity after immersion: 7.8*10^8Ω·cm
[0126] 3. Tensile strength loss rate
[0127] Comparative Example 1: 3.6%
[0128] Example 1: 2.5%
[0129] 4. Analysis of the causes of performance differences
[0130] ①Electrostatic voltage decay time
[0131] No antistatic agent was added in Comparative Example 1, so an effective conductive layer could not be formed on the surface of the material. The polyurethane material itself has a high insulation performance and is prone to accumulate static charge, resulting in a long static voltage decay time.
[0132] In Example 1, an antistatic agent is added. The hydrophilic groups (such as hydroxyl -OH) and polar groups (such as carboxyl -COOH) in the antistatic agent can adsorb water molecules in the environment to form a layer of water film, thereby increasing the electrical conductivity of the material surface, thereby accelerating the release of static charge and significantly shortening the static voltage decay time.
[0133] ②Volume resistivity before and after fuel immersion
[0134] The volume resistivity of Comparative Example 1 changed significantly before and after fuel immersion, increasing from 1.110^13Ω·cm to 2.610^15Ω·cm. This is because the surface insulation performance of the material without antistatic agent was further enhanced after fuel immersion, resulting in a significant increase in volume resistivity.
[0135] The volume resistivity of Example 1 before and after fuel immersion changed slightly, increasing from 5.110^8Ω·cm to 7.810^8Ω·cm. The addition of the antistatic agent enables the material to maintain a low volume resistivity after fuel immersion and maintain good conductive properties.
[0136] ③Tensile strength loss rate
[0137] The tensile strength loss rate of Comparative Example 1 is 3.6%, which is slightly higher than 2.5% of Example 1, but still within a reasonable range. This shows that even without an antistatic agent, the mechanical properties of the material after fuel immersion are still good.
[0138] The tensile strength loss rate of Example 1 is 2.5%, indicating that the material can still maintain a high mechanical strength after being soaked in fuel. The addition of antistatic agent does not significantly affect the mechanical properties of the material, which may be due to the moderate amount of antistatic agent used, which does not have a negative impact on the matrix properties of the material.
[0139] The polyurethane barrier explosion suppression material of Comparative Example 1 is significantly inferior to that of Example 1 in terms of antistatic performance, mainly due to the lack of antistatic agent. The addition of antistatic agent not only significantly improves the antistatic performance of the material, but also maintains the mechanical properties and chemical resistance of the material to a certain extent. Therefore, the material of Example 1 has higher safety and reliability in practical applications, and is more suitable for use in occasions such as fuel tanks that require high safety protection.
[0140] 2. Comparative Example 2 is compared with Example 1:
[0141] 1. Static voltage decay time
[0142] Comparative Example 2: The static voltage decay time is less than 10 minutes.
[0143] Embodiment 1: The static voltage decay time is less than 10 minutes.
[0144] 2. Volume resistivity before and after fuel immersion
[0145] Comparative Example 2:
[0146] Volume resistivity before immersion: 1.5*10^9Ω·cm
[0147] Volume resistivity after immersion: 2.3*10^11Ω·cm
[0148] Embodiment 1:
[0149] Volume resistivity before immersion: 5.1*10^8Ω·cm
[0150] Volume resistivity after immersion: 7.8*10^8Ω·cm
[0151] 3. Tensile strength loss rate
[0152] Comparative Example 2: 5.8%
[0153] Example 1: 2.5%
[0154] 4. Analysis of the causes of performance differences
[0155] ①Electrostatic voltage decay time
[0156] The static voltage decay time of Comparative Example 2 and Example 1 is less than 10 minutes, which meets the standard requirements. This shows that the material of Comparative Example 2 also has good antistatic performance after adding the antistatic agent.
[0157] Reason for the difference: Although the static voltage decay time of Comparative Example 2 meets the standard, its value is close to 10 minutes, indicating that its antistatic performance is slightly inferior to that of Example 1. This may be because the amount of antistatic agent used in Comparative Example 2 is small, or the distribution of the antistatic agent is not uniform, resulting in a slightly poor antistatic effect.
[0158] ②Volume resistivity before and after fuel immersion
[0159] The volume resistivity of Comparative Example 2 changed significantly before and after fuel immersion, increasing from 1.510^9Ω·cm to 2.310^11Ω·cm. This shows that after fuel immersion, the volume resistivity of the material increased significantly and the antistatic performance decreased.
[0160] The volume resistivity of Example 1 before and after fuel immersion changed slightly, increasing from 5.110^8Ω·cm to 7.810^8Ω·cm. This shows that the material can still maintain a low volume resistivity and good antistatic performance after fuel immersion.
[0161] Reason for the difference: The volume resistivity of Comparative Example 2 increased significantly after fuel immersion, which may be due to insufficient amount of antistatic agent or uneven distribution of antistatic agent in the material, resulting in its gradual failure during fuel immersion. In Example 1, the amount of antistatic agent used is moderate and evenly distributed, and it can maintain good antistatic performance after fuel immersion.
[0162] ③Tensile strength loss rate
[0163] The tensile strength loss rate of Comparative Example 2 is 5.8%, which is significantly higher than 2.5% of Example 1. This indicates that the mechanical properties of the material of Comparative Example 2 are significantly reduced after being soaked in fuel.
[0164] The tensile strength loss rate of Example 1 is 2.5%, indicating that the material can still maintain a relatively high mechanical strength after being immersed in fuel.
[0165] Reasons for the difference: The tensile strength loss rate of Comparative Example 2 is higher, which may be because the addition of the antistatic agent has an adverse effect on the matrix properties of the material, or the compatibility of the antistatic agent with the matrix material is poor, resulting in a decrease in the mechanical properties of the material after being soaked in fuel. In Example 1, the amount and selection of the antistatic agent are more reasonable, and it can be well compatible with the matrix material, so that the mechanical properties of the material are not affected while maintaining the antistatic properties.
[0166] Although the polyurethane barrier explosion suppression material of Comparative Example 2 basically meets the standards in terms of antistatic performance, it performs poorly in terms of volume resistivity and tensile strength loss rate after fuel immersion. This is mainly because the amount of antistatic agent used is insufficient or the distribution is uneven, which causes it to gradually fail during the fuel immersion process. At the same time, the addition of the antistatic agent has a certain negative impact on the matrix properties of the material. In contrast, the material of Example 1 performs well in terms of antistatic performance, volume resistivity and tensile strength loss rate after fuel immersion, which is due to the reasonable amount and good distribution of the antistatic agent, as well as the good compatibility of the antistatic agent with the matrix material. Therefore, the material of Example 1 has higher safety and reliability in practical applications, and is more suitable for use in fuel tanks and other occasions that require high safety protection.
[0167] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present application should be included in the protection scope of the present application.
Claims
1. Polyurethane barrier explosion suppression material with antistatic properties, characterized in that: The invention comprises the following raw materials in parts by weight: 100-150 parts of polyether triol, 60-80 parts of polyester polyol, 10-15 parts of isocyanate, 3-5 parts of foaming agent, 1-3 parts of stabilizer, 1-3 parts of catalyst, 5-10 parts of coupling agent, 10-15 parts of antistatic agent; The preparation method of the antistatic agent comprises the following steps: Ethylene glycol monovinyl ether and dimethyl maleate are uniformly mixed, dimethyl carbonate and 1% by weight of 2,2'-azobisisobutyronitrile of ethylene glycol monovinyl ether are added, and the mixture is reacted at 65° C. for 12 hours to obtain the antistatic agent.
2. The polyurethane barrier explosion suppression material according to claim 1, characterized in that: The feeding molar ratio of ethylene glycol monovinyl ether and dimethyl maleate is 1:
1.
3. The polyurethane barrier explosion suppression material according to claim 1, characterized in that: The polyester polyol is poly(diethylene glycol adipate) diol.
4. The polyurethane barrier explosion suppression material according to claim 1, characterized in that: The polyether triol is obtained by ring-opening polymerization of 1,2-propylene oxide using propylene glycol as an initiator.
5. The polyurethane barrier explosion suppression material according to claim 1, characterized in that: The isocyanate is polymethylene polyphenyl isocyanate.
6. The polyurethane barrier explosion suppression material according to claim 1, characterized in that: The foaming agent is water.
7. The polyurethane barrier explosion suppression material according to claim 1, characterized in that: The stabilizer is dimethyl silicone oil.
8. The polyurethane barrier explosion suppression material according to claim 1, characterized in that: The coupling agent is a titanate coupling agent.
9. The method for preparing the polyurethane barrier explosion suppression material according to any one of claims 1 to 8, characterized in that: The following steps are involved: S1. Preparation of antistatic agent Ethylene glycol monovinyl ether and dimethyl maleate are uniformly mixed, dimethyl carbonate and 1% by weight of 2,2'-azobisisobutyronitrile of ethylene glycol monovinyl ether are added, and the mixture is reacted at 65° C. for 12 hours to obtain an antistatic agent; S2. Foaming treatment Take 100-150 parts of polyether triol, 60-80 parts of polyester polyol and 10-15 parts of isocyanate, put them into a reactor for thorough mixing, heat them to 55°C under a nitrogen environment, and react at 55°C for 2-3 hours; then add 3-5 parts of foaming agent, 1-3 parts of stabilizer, 1-3 parts of catalyst, 5-10 parts of coupling agent and 10-15 parts of antistatic agent into the reactor, mix them thoroughly, heat them to 110-120°C, and react for 10-20 minutes; after the reaction is completed, cool them to room temperature to obtain a polyurethane barrier explosion suppression material.
10. Application of polyurethane barrier explosion suppression material with antistatic properties, characterized in that: The polyurethane barrier explosion suppression material according to any one of claims 1 to 8 or the polyurethane barrier explosion suppression material prepared by the preparation method according to claim 9 is used as a filling material in a fuel tank.